2017
DOI: 10.20959/wjpr20178-8631
|View full text |Cite
|
Sign up to set email alerts
|

Bioplastic (Poly -3-Hydroxybutyrate) Production by Local Pseudomonas Aeruginosa Isolates Utilizing Waste Cooking Oil

Abstract: Disposal of domestic wastes, such as waste cooking oil (WCO), without pretreatment, contributes to the deterioration of the environment and creating severs problems. Synthetic plastic poses threat to the environment, because it is non-biodegradable are now accumulate in the environment at great millions of tons per year.Bioplastic are polymers such as Poly -3-hydroxybutyrate (PHB), which has gained importance since it can be easily degrade in nature. The present study was aimed to isolate a promising microbial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…In a similar study, Abid et al reported 50.27% PHA production by Pseudomonas aeruginosa using soybean oil (67). Gatea et al reported 100 mg/L PHA production by Pseudomonas aeruginosa using waste cooking oil (68). Although both previous studies and this study use fatty acids for PHA production, bioconversion pathways for vegetable oil and animal fat oil could be different (24,69).…”
Section: Discussionmentioning
confidence: 64%
“…In a similar study, Abid et al reported 50.27% PHA production by Pseudomonas aeruginosa using soybean oil (67). Gatea et al reported 100 mg/L PHA production by Pseudomonas aeruginosa using waste cooking oil (68). Although both previous studies and this study use fatty acids for PHA production, bioconversion pathways for vegetable oil and animal fat oil could be different (24,69).…”
Section: Discussionmentioning
confidence: 64%